Implementation of Pre-Order via Request Item Sales Using Carefully Designed Pre-Sales Steps to Enhance E-Commerce Effectiveness: an Indonesian SME Case Study - Jaswadi; Andi Kusuma Indrawan; Retnaning Ayu Dyah Sawitri (International Journal Of Community Service, 2023)
Fashion products, which currently dominate the online market in Indonesia as products that are frequently purchased, are in fact not yet facilitated by an e-commerce system that is capable of serving pre-order sales of fashion products at the buyer's request. Therefore, most of the ineffective activities occur in the pre-sales stage because it can lead to long interactions with customers to get the requested information, and sales quotations cannot be processed immediately. Therefore, the purpose of this study is to analyze the quality of e-commerce that was developed specifically to serve these sales through real implementation for Sakinah_id SMEs and buyers who actually want to order product requests. Based on assessments from buyers and MSME employees, the e-commerce used can cut time faster in the pre-sales stage, and delivery of sales quotations can be done immediately to buyers. The durability of shorter service and processing times is felt, especially when the number of orders coming in is large. So that it can help reduce the burden on the employee concerned through the implementation of this e-commerce.